A Model for Assessing Sustainability and Performance Improvement of Countries via Data Envelopment Analysis - Sara yousefi; Zohreh Mousavi Kashi (پژوهش‌های برنامه و توسعه)
In recent years, sustainable development has been considered by international communities as an important issue in changing management, promoting infrastructure and increasing capabilities of each country. Sustainable development has two components of “development and essentials of sustainability”, and sustainability is comprised of three major economic, social and environmental dimensions. Nowadays, due to increasing population, the world faces complex economic, social and environmental crises. Legal authorities are also pushing industries to pay attention to sustainability. Therefore, organizations and countries strive to improve their sustainability performance. Due to the importance of this subject, this paper developed SORM integrated data envelopment analysis model and SORM integrated inverse data envelopment analysis model to evaluate the sustainability of countries and to provide improvement values for more sustainability. In integrated SORM model, sustainability of 24 countries is calculated with simultaneous consideration regarding inputs and outputs. In the integrated inverse SORM model, optimal changes of inputs and outputs are presented, while efficiency or sustainability are kept unchanged. The optimal changes presented to countries have been in line with the goals of sustainable development and the goals pertaining to achieving long-term global development. Eventually, performance improvements in two countries, Germany and Iran, are compared. The results indicate the decrease or stability of undesirable inputs and outputs and the increase or stability of desirable inputs and outputs.